Potential acidity determination for soils with high soil organic matter - Douglas Luiz Grando; Lucas Peranzoni Deponti; Marcos de Lima Rodrigues; Cauan Guerra Martins; William Natale; Djalma Eugenio Schmitt; Gustavo Nogara de Siqueira; Natália Moreira Palermo; João Kaminski; Gustavo Brunetto (Revista Brasileira de Ciência do Solo)
ABSTRACT Lime applications are used in acid soils to correct pH and eliminate Al3+ toxicity in crops. The lime rates are determined based on the estimated soil potential acidity (H+Al), using soil incubations with calcium carbonate (CaCO3) for 180 days, being a time-consuming and laborious process. An alternative method with calcium hydroxide [Ca(OH)2] for 96 h incubation may efficiently estimate H+Al, but it needs further studies. Also, soils from specific regions in southern Brazil have high organic matter (SOM) contents (>5 %), medium clay contents (20-40 %), and are stony, lacking research to improve liming recommendations. The study aimed to determine potential acidity and adjust lime rates for acidity correction in medium-textured soils with high SOM and stoniness in the Serra Gaúcha region (RS), Brazil, and to test the efficiency of the short incubation alternative method. For this purpose, 20 native forest soils were sampled in the 0.00-0.20 m layer. Samples were dried, sieved, and subjected to short and long incubations. The H+Al values obtained through the incubations were compared with the Manual de calagem e adubação para os Estados do Rio Grande do Sul e de Santa Catarina (CQFS-RS/SC, 2016) equation. The H+Al values estimated by CQFS-RS/SC were lower than those determined by the long incubation, indicating lime rates ranging from 2.0 to 5.1 Mg ha-1 lower than in the long incubation. The short incubation showed a positive correlation (0.93***) with the long incubation. The potential acidity for soil water pH 6.5 can be obtained by long [H+Al (cmolc dm-3) = 1354.9e-0.855TSM] and short [H+Al (cmolc dm-3) = 3763.8e-1.086TSM] incubations, in which TSM is the Tampão Santa Maria index. On average, 34 % of the soil volume was composed of rock fragments (>2 mm). We recommend adjusting the limestone rates for soils with stoniness, considering only the percentage of soil in the diagnostic layer (SDL%).